Health promotion in elderly patients with hyponatremia related to polypharmacy: The role of nurses (International Seven Journal of Health Research, 2023)
Hyponatremia is a condition of low sodium concentration in the body, which occurs occasionally in the long-lived, with greater aggravation in a scenario of poly-medications. Objective: To analyze articles on the topic: The importance of nurses' role in promoting health in elderly people with hyponatremia. Method: This work is a systematic bibliographical review of integrative evaluation. The results show the necessary correlation between professional development, the characteristics of elderly people with hyponatremia and their implications in terms of medication. Nurses are the main agents in health promotion, knowing all the particularities of their patients, planning, implementing and participating in the whole process. This work was developed with the aim of raising awareness and providing learning for professionals, so that they are more engaged and participate in a more assertive way in promoting the health of the population in which they work.